Clinicopathologic and prognosis of 30 patients with FH-deficient renal cell carcinoma: a single-center retrospective study - Junjie Bai; Jianjia Huang; Yushi Ye; Jun Lin; Yahui Wen; Zicheng Cai; Peihuang Chen; Tong Shangguan; Gaoyu Zou; Qianyi Qiu; Ru Chen; Rong Liu; et al. (BMC Cancer)
Abstract Background FH-Deficient Renal Cell Carcinoma (FH-RCC) is a rare, aggressive cancer with poor prognosis and treatment challenges. Immunohistochemical (IHC), including PD-1, PD-L1, PD-L2, and CTLA-4, play a key role in survival outcomes and therapeutic decisions, highlighting the need to evaluate their significance in FH-RCC. Methods The expression of IHC including PD-1, PD-L1, PD-L2 and CTLA-4 in tumor cells was evaluated. The clinicopathological and therapeutic information of 30 patients with FHRCC was retrospectively collected and correlation analysis and Kaplan-Meier analysis were performed. Results In a cohort of 30 patients with FHRCC, the majority of tumors exhibited a simple papillary structure. PD-1 positive expression was observed in 43.3% (13/30) of the patients, PD-L1 in 53.3% (16/30), PD-L2 in 20.0% (6/30), and CTLA-4 in 90%. CK-7 showed positive expression in 23.3% of the patients. Notably, PD-L1 positivity was associated with a higher frequency of simple papillary structures and better outcomes in patients receiving TKI monotherapy. Conversely, patients who underwent radical surgery, exhibited negative CK-7 expression, had positive PD-1 expression, and negative PD-L2 expression, demonstrated shorter disease-free survival (DFS). Additionally, those who underwent radical surgery and were PD-L2 negative had worse cancer-specific survival (CSS). Conclusion FH-RCC is highly aggressive and has a poor prognosis, and clinical and pathologic parameters such as IHC expression including PD-1, PD-L1, PD-L2 and CTLA-4 have a predictive value in prognosis and treatment.